Live Birth Rate in Patients With Premature Ovarian Insufficiency During Long-Term Follow-Up Under Hormone Replacement With or Without Ovarian Stimulation - Ishizuka, Bunpei; Furuya, Masataka; Kimura, Machiko; Kamioka, Eri; Kawamura, Kazuhiro (Frontiers in Endocrinology, 2021)
We analyzed data from 466 patients with premature ovarian insufficiency (POI) who wished to have a biological child and were followed up while undergoing hormone replacement (HR) therapy with or without ovarian stimulation (OS) between April 2014 and December 2020. OS was conducted in 6891 cycles in 429 patients (Group OS), whereas only HR (Group HR) was conducted in 1117 cycles in 37 patients. The follicle growth rate was 48.3% (207/429) per patient in Group OS and 5.4% (2/37) in Group HR (p<0.01). There were 51 live births (LBs) in 50 patients during follow-up. In Group OS, the LB rate was 5.8% (47/807) in cycles where in vitro fertilization (IVF) and embryo transfer were attempted (Group IVF), and 1.3% (3/236) in cycles where intrauterine insemination/timed intercourse was attempted (p<0.01). No pregnancies occurred in Group HR. Among the patients in Group IVF, the LB rate was significantly higher in patients aged <35 years at the initiation of follow-up than in patients who started at later ages (p<0.01). Among the cases who achieved an LB, 39 were patients with idiopathic POI (Group IVF-1, n=297) and seven were patients who had undergone surgical treatment for benign ovarian tumors (Group IVF-2, n=50); however, no LBs occurred in patients who had undergone treatment for malignancy (n=17), and only one in patients with chromosomal abnormalities (n=22). The LB rate per case in the patients in Group IVF-1 and those aged <35 years at the start of follow-up (Group IVF-1-a) was 24.1% (26/108), which was higher than those of the other age groups. The LB rate per case in the patients in Group IVF-1-a with <4 years of amenorrhea was 37.3% (19/51), and that in the patients in Group IVF-2 with <4 years of amenorrhea was 21.2% (7/33). These results suggest that infertility treatment is possible in some patients with POI, especially those that can be classified in Group IVF-1-a and Group IVF-2 with <4 years of amenorrhea. Therefore, OS combined with HR therapy should be considered for such patients before attempts at oocyte donation.